2011
DOI: 10.1007/s00068-011-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy-based surgical strategy of gastrointestinal fistula treatment

Abstract: Anatomic delineation of a gastrointestinal fistula is essential in assessing the likelihood of spontaneous closure or to plan the surgical management. Computed tomography (CT) enterography and/or fistulograms provide invaluable information. The surgical strategy should carefully consider the when and how, as well as the special clinical situations that may arise following radiotherapy, the inaccessible or "frozen abdomen", and enteroatmospheric fistulas (EAFs). New operations like those performed in bariatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Some papers 14–16 present images of enterocutaneous fistulas taken from CT. However, when combining CT slices to form a volumetric body, the resolution of the wound surface is lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers 14–16 present images of enterocutaneous fistulas taken from CT. However, when combining CT slices to form a volumetric body, the resolution of the wound surface is lost.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical results of the application of this therapy have been widely described by Durán Muñoz-Cruzado et al 13 from our working group, which corroborates the efficacy and safety of the application of the device generated by the methodology presented in this work. Some papers [14][15][16] present images of enterocutaneous fistulas taken from CT. However, when combining CT slices to form a volumetric body, the resolution of the wound surface is lost.…”
Section: Treatment Effectivenessmentioning
confidence: 99%
“…dressing. In small and superficial EAFs without visible mucosa, suture with subsequent coverage of the suture line with fibrin glue, acellular dermal matrix or autologous split skin graft may be successful without any additional risks (15,44). Jamsidi et al reported 5/7 EAFs closed in this way (71.4%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is difficult for the skin to overlap the margins of the intestinal perforation so as to cover and close it. According to the literature [6], the best way to transform the fistula tract is when it is in a kind of ''well,'' where the bowel lies at least 2 cm below skin level and is surrounded by granulation tissue, so that musculocutaneous/subcutaneous and cutaneous circumferential tissues can coalesce, reduce, and cover the defect. When the fistula is very deep, the patient is fed parenterally, and, provided that the bowel is not obstructed, good healing and closure take place almost spontaneously.…”
Section: Discussionmentioning
confidence: 99%